Sex differences in waist circumference obesity and eating speed: a cross-sectional study of Japanese people with normal body mass index - Yaguchi, Yuri; Konta, Tsuneo; Imaeda, Nahomi; Goto, Chiho; Ueno, Yoshiyuki; Kayama, Takamasa (Frontiers in Nutrition, 2024)
Background: Fast eating has been positively associated with visceral fat accumulation in normalweight individuals according to body mass index (BMI). However, previous studies have not examined energy and nutrients, or adjusted for food intake. We examined the relationship between eating speed and visceral fat accumulation, using waist circumference as an index, in middle-aged participants who were considered to be of standard weight according to BMI, with nutrient intake added as an adjustment factor.We included 6548 Japanese participants (3875 men and 2673 women) aged 40-74 years with BMI 18.5-25.0 kg/m 2 who were enrolled in the Yamagata Cohort Study. Participants were divided into "fast," "normal," and "slow" eaters according to self-reported eating speed. Nutrient and food intake were evaluated using a food frequency questionnaire, and the difference in intake by eating speed and sex was compared. Logistic regression analysis was used to examine the relationship between waist circumference obesity (men ≥85 cm, women ≥90 cm, according to Japanese criteria) and eating speed, adjusted for nutrient intake and other lifestyle habits. Results: In men, slow eaters had greater intakes of dietary protein, fat, polyunsaturated fatty acids (PUFA), omega-3 PUFA, total dietary fiber, soluble dietary fiber, insoluble dietary fiber, soybean products, fish, green and yellow vegetables, other vegetables, mushrooms, and seaweed in comparison with normal-speed eaters. In men, waist circumference obesity was significantly lower among slow eaters than in the group with normal eating speed. In women, waist circumference obesity was not significantly associated with eating speed and was not also associated with nutrient/food consumption except omega-6 PUFA.Eating slowly was associated with healthy dietary habits. Our results could help prevent waist circumference obesity in men with a BMI between 18.5 and 25.0 kg/m 2 . However, similar findings were not observed in women, suggesting a sex difference.